2011
DOI: 10.1248/jhs.57.367
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Quinolinic Acid after Exercise in Mice: Implications for Sensation of Fatigue after Exercise

Abstract: We have previously hypothesized that mental fatigue is caused by neuronal brain damage through the activation of N-methyl-D-aspartate receptors by quinolinic acid (QUIN). QUIN is a metabolite of tryptophan in the kynurenine pathway; this pathway is stimulated by several cytokines, including tumor necrosis factor (TNF)-α. Recently, we proved this mental-fatigue hypothesis by studying stress-loaded and lipopolysaccharide-treated mice. In the present study, we measured blood QUIN levels after exercise in mice to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…11,12) Therefore, in the present study, we investigated whether QUIN also participates in causing combined (physical and mental) fatigue using an animal model in which rats were housed under water-immersed conditions. The swimming time of the water-immersed group was shorter than Rats were housed individually for 5 d in a plastic cage filled with 23°C water to a height of 1.5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12) Therefore, in the present study, we investigated whether QUIN also participates in causing combined (physical and mental) fatigue using an animal model in which rats were housed under water-immersed conditions. The swimming time of the water-immersed group was shorter than Rats were housed individually for 5 d in a plastic cage filled with 23°C water to a height of 1.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…11) In addition, in a recent study of exercise-loaded mice, we have suggested that QUIN also participates in the sensation of fatigue after exercise, which partly resembles mental fatigue in terms of lassitude, sleepiness and decreased motivation. 12) Therefore, in the present study, we investigated whether the same mechanism also participates in causing combined fatigue. In addition, memantine (MEM), an NMDA receptor antagonist, was administered to study the possibility of NMDA receptor involvement in the neuronal brain damage of combined fatigue.…”
mentioning
confidence: 96%
“…[112][113][114] An increase in plasma kynurenine can enhance cerebral kynurenine levels leading to production of neuroactive kynurenine metabolites with potential behavioral consequences. Blood QA is also increased by exercise and it has been suggested that QA can cross the BBB, 115 which is weakened by exercise. 116 Tumor necrosis factor α, whose serum levels are increased by exercise, 112,115 has previously been shown to impair BBB permeability.…”
Section: Other Effects Of Exercisementioning
confidence: 99%
“…Blood QA is also increased by exercise and it has been suggested that QA can cross the BBB, 115 which is weakened by exercise. 116 Tumor necrosis factor α, whose serum levels are increased by exercise, 112,115 has previously been shown to impair BBB permeability. 117,118 Furthermore, 40% to 50% of brain QA is of peripheral origin.…”
Section: Impact Of Exercisementioning
confidence: 99%
“…Of note, many studies have demonstrated that acute bouts of exercise do in fact result in a proinflammatory response characterized by leukocytosis and elevations in proinflammatory mediators [ 81 - 83 ]. An acutely elevated rate of TRP metabolism and resulting increase in serum kynurenine concentrations have also been demonstrated and have been suggested to relate to a cytokine-induced up-regulation of IDO [ 84 , 85 ]. Further, exercise is known to result in an acute elevation in glucocorticoids [ 86 ] which have been suggested to induce the up-regulation of TDO2, further contributing to the elevated rate of TRP metabolism during exercise [ 87 ].…”
Section: Introductionmentioning
confidence: 99%